2020
DOI: 10.1002/cb.1807
|View full text |Cite
|
Sign up to set email alerts
|

Theorising the emerging green prosumer culture and profiling green prosumers in the green commodities market

Abstract: This paper explores the phenomenon of green prosumption with a view to theorising the phenomenon and highlighting the challenges and opportunities this particular subculture creates for marketers of green commodities. Narratives of young green prosumers were gathered from 18 phenomenological in‐depth interviews. Capturing green prosumer experiences and subjective meanings, three thematic categories of green prosumption practices, (a) contraction, (b) control, and (c) creation, are postulated in the study. It a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 87 publications
0
23
0
1
Order By: Relevance
“…As time goes on, prosumers are thought to be both the value creators and the altruistic value sharers. Existing studies have clearly shown that the phenomenon of prosumption is an evolutionary process and a conceptual shift from consumers to prosumers [21], and some researchers even suggest that "prosumer" will replace the notion of "consumer" [22].…”
Section: Platform Economy and Business Modelmentioning
confidence: 99%
“…As time goes on, prosumers are thought to be both the value creators and the altruistic value sharers. Existing studies have clearly shown that the phenomenon of prosumption is an evolutionary process and a conceptual shift from consumers to prosumers [21], and some researchers even suggest that "prosumer" will replace the notion of "consumer" [22].…”
Section: Platform Economy and Business Modelmentioning
confidence: 99%
“…Defining prosumers for COVID-19 and other contexts Academics have embraced various conceptualizations of prosumers (Cova and Cova, 2012;Kotler, 1986;Setiffi et al, 2018;Toffler, 1980) but there is a surprising absence of clear definitions of prosumers (Perera et al, 2020). Our proposed definition is versatile as it applies to crises and non-crises contexts.…”
Section: Structure Of the Papermentioning
confidence: 99%
“…their focus on themselves, customizing prosumers are unlikely to have been a major factor in addressing challenges caused by COVID-19. Typically prosumers have been thought of as providing value for others, particularly through technology (Andrews and Ritzer, 2018;Darmody et al, 2017;Perera et al, 2020). Therefore, we label the fourth prosumer archetype "collaborative prosumers".…”
Section: Prosumers In Times Of Crisismentioning
confidence: 99%
“…While prosumption is an antecedent of value co-creation (Chandler & Chen, 2015;Prahalad & Ramaswamy, 2004), they are not interchangeable concepts (Alhashem et al, 2021). Prosumers do not necessarily rely on second parties to (co-)create value, nor are they always concerned with value creation, and prosumption is not necessarily mutually beneficial (Eckhardt et al, 2019;Lang et al, 2020;Perera et al, 2020). Thus, prosumption is not necessarily positive, like value co-creation.…”
Section: Introductionmentioning
confidence: 99%